Sistem Informasi Penjualan Motor Bekas Berbasis Android Untuk Meningkatkan Penjualan di Mokascirebon.Com - Agis Maulana Robani; Saepul Hadi; Odi Nurdiawan; Gifthera Dwilestari; Nana Suarna (STMIK Budi Darma, 2021)
Mokascirebon.com is a trusted showroom in Cirebon for buying and selling second hand motorcycle, where in the business of buying and selling second hand motorcycle, it requires a large amount of capital and must be able to turn in and out of the motorcycle quickly considering that the longer the motorcycle is sold, the price will be decreased, and also if the tax of motorcycle stocks are in due date, it will increase the capital costs which is needed. The length of time a motorcycle has been sold has many factors, including tight business competition, where all of them are competing to increase sales of their second hand motorcycle and also have a system that makes working faster and more precise. From those problems, an idea is emerged to increase the motorcycle sales by increasing the reach of promotional media on the Android platform and creating an Android based computerized system that is able to accelerate the internal work of the company. In designing this application using the waterfall method, where the stages are gathering needs, building and evaluating waterfall, coding, testing, evaluating the system until finally the system can be used. The programming language used is Java and also uses the Android Studio application to create the Android application. The database used is MySQL. The supporting tools used are Photoshop, Corel Draw and the Android Emulator. With this android based second hand motorcycle sales information system to Increase Sales at Mokascirebon.com, it is hoped that it will be able to increase sales of second hand motorcycle and to simplify and accelerate the company's internal work